Associations between leukocyte telomere length and three measures of folate status: a cross-sectional analysis of NHANES 1999–2002 - Xue, Qian; Chen, Hongju (Frontiers in Nutrition, 2026)
BackgroundShortening of leukocyte telomere length (LTL) is a core hallmark of cellular senescence. Folate provides essential methyl groups for DNA synthesis and repair, theoretically capable of slowing telomere attrition by maintaining genomic integrity. However, current epidemiological studies on folate and LTL are still limited, and most prior investigations have relied on a single metric of folate status.ObjectiveThis study aimed to investigate the associations between LTL and three measures of folate status, dietary intake, serum folate and red blood cell (RBC) folate, to provide more precise epidemiological evidence of folate's role in cellular aging and to establish a scientific basis for potential nutritional intervention strategies.MethodsThis cross-sectional analysis included 7,324 participants from the National Health and Nutrition Examination Survey (NHANES) 1999–2002. Multivariable linear regression models, adjusted for demographic, lifestyle, and nutritional factors, were used to assess associations. Restricted cubic splines and piecewise linear regression were employed to evaluate non-linear relationships.ResultsAfter full adjustment, both serum and RBC folate showed positive linear associations with longer LTL (P for trend < 0.05). Dietary folate exhibited a non-linear relationship with LTL (P for non-linearity < 0.05). Meeting the recommended intake (≥400 μg/day) was associated with longer telomeres (β = 0.05, 95% CI: 0.03–0.06). A saturation effect was observed; beyond 500.86 μg/day (95% CI: 490.71–511.01), further intake did not significantly increase LTL.ConclusionAdequate folate status is associated with longer telomeres, supporting a role in mitigating cellular aging. Dietary intake ≥400 μg/day is beneficial, but exceeding ~500 μg/day offers no further advantage.